Measuring and communicating security's value : a compendium of metrics for enterprise protection - Campbell, George, 1942- (Amsterdam, Netherlands : Elsevier, 2015)
In corporate security today, while the topic of information technology (IT) security metrics has been extensively covered, there are too few knowledgeable contributions to the significantly larger field of global enterprise protection. Measuring and Communicating Security's Value addresses this dearth of information by offering a collection of lessons learned and proven approaches to enterprise security management. Authored by George Campbell, emeritus faculty of the Security Executive Council and former chief security officer of Fidelity Investments, this book can be used in conjunction with Measures and Metrics in Corporate Security, the foundational text for security metrics. This book builds on that foundation and covers the why, what, and how of a security metrics program, risk reporting, insider risk, building influence, business alignment, and much more.
Measuring progress of annual plans and objectivesis compliance a key risk indicator or a key performance indicator?; security contract compliance auditing; measuring for integrity: background investigations; measuring executive protection programs; business unit criticality, resilience, and continuity planning; measuring security awareness programs; the absence of awareness is a key contributor to risk; ability to influence the business is a key performance indicator; security's value proposition: value is a key performance indicator
Includes index.
Vendor-supplied metadata.
Elsevier
Keywords: Corporations -- Security measures -- Evaluation; Security systems -- Management; Private security services -- Evaluation; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Business; Leadership; Management; Electronic books; Electronic books